Non-homeostatic intake of snack foods: Molecular triggers and effects on brain activity pattern - Hoch, Tobias; Heß, Andreas; Pischetsrieder, Monika (The Chemical Sensory Informatics of Food: Measurement, Analysis, Integration, 2015)
Craving for special types of food like snack food can tremendously influence our energy balance. The result: obesity due to a non-homeostatic, hedonic food intake, i.e. an intake of energy independent of hunger and satiety. The intake of potato chips – an often craved highly palatable snack food – has a great influence on whole brain activity pattern. Especially the reward system as well as circuits regulating food intake, sleep and locomotor activity are affected. Furthermore, we could show that the fat and carbohydrate content is a main contributor to the palatability of potato chips. These first steps of the identification of the molecular triggers and the corresponding effects on brain activity pattern of the non-homeostatic intake of highly palatable snack food are reviewed in this chapter.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.nonhom